Preoperative and Postoperative Imaging in Idiopathic Scoliosis: What the Surgeon Wants to Know - Guglielmi, Riccardo; Di Chio, Teresa; Kaleeta Maalu, Jean-Paul; Aparisi Gómez, Maria Pilar; De Leucio, Alessandro; Simoni, Paolo (Seminars in Musculoskeletal Radiology, 2021)
The term idiopathic scoliosis covers a broad spectrum of spinal deformities in the pediatric population without an underlying congenital anomaly of the spine. Depending on the age of presentation, it has both characteristic clinical and imaging features and a different prognosis. The radiologist should provide the surgeon with critical information to assess the degree of deformity and eventually plan surgery. Thoracic deformities and lung volume must also be part of the preoperative assessment. Imaging has a critical role in postsurgical follow-up and in surgical complications. This review highlights the importance of common terminology and measurement methods to avoid incongruences. The different imaging modalities are discussed with their indications and limitations. We pay special attention to imaging modalities that can help the surgeon assess skeletal maturation reliably and thus predict the prognosis of scoliosis. Radiation protection and the risk of cumulative radiation exposure in these patients is emphasized.
Keywords: children; magnetic resonance imaging; scoliosis; radiographs; computed tomography